A Novel Multielement, Multiphase, and B‐Containing SiOx Composite as a Stable Anode Material for Li‐Ion Batteries. Issue 5 (11th January 2019) - Yang, Wen; Liu, Huan; Ren, Zhuanghe; Jian, Ni; Gao, Mingxia; Wu, Yongjun; Liu, Yongfeng; Pan, Hongge
Abstract: In this study, a novel B‐containing SiO x composite is demonstrated with a remarkably improved cycling performance as a stable anode material for lithium‐ion batteries. A multielement, multiphase, B‐containing SiO x composite is successfully prepared by heating a mixture of SiO and LiBH4 to 500 °C. The resultant product consists mainly of amorphous/nanocrystalline Si, SiO x, B, B2 O3, and Li2 SiO3 . The in situ formed amorphous B, B2 O3, and nanocrystalline Li2 SiO3 mostly remain at the surface of the product particles, providing a remarkable enhancement in the mechanical properties of the Si/SiO x active materials. This feature provides good accommodation for the volume change during lithiation/delithiation, consequently depressing the pulverization and fracture of the Si/SiO x active materials. As a result, the cycling stability of the prepared B‐containing SiO x composite is significantly improved. The sample prepared from SiO–0.3LiBH4 delivers reversible capacity of 1186 mAh g −1 at 100 mA g −1 after 100 deep cycles, corresponding to the capacity retention of 81%. This outcome is more than two times higher than that of pristine SiO (33.9%). Abstract : A multielement, multiphase, B‐containing SiO x composite is successfully prepared by a thermally activated chemical reaction between SiO and LiBH4 . The resultant products exhibit remarkably improved cycling stability due to good accommodation for the volume change during lithiation/delithiation caused by the in situ formed amorphous B, B2 O3, and nanocrystalline Li2 SiO3 .